Single-State NWFZs – a response to NWFZ blind spots - Enkhsaikhan, J (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.20 Mongolian Journal of International Affairs No.14 2007 pp.32-36